Book endS & Odd Books. - Walter Phillips Gallery, The Banff Centre School of Fine Arts, Banff (Banff : Walter Phillips Gallery - The Banff Centre for the Arts Banff, 1993)
Baychar ; Cortright, Steven ; Curnoe, Greg ; Drescher, Henrik ; Dunning, Alan ; Egerer, Evelyne ; Henricks, Nelson ; Irwin ; Lohr, Helmut ; Matsubara ; McCaffrey, Steve ; Piper, Adrian ; Purdy, Richard ; Laurie Simmonw ; Skelton, Carl ; Soler, José ; Williams, Emmett ; Wu, Kira ; etc.
Book endS & Odd Books, Walter Phillips Gallery, The Banff Centre for the Arts, Banff, 28 October 1993 to 30 January 1994
boek